Clinical correlates of the ability to consent to research participation in brain metastasis. Issue 10 (11th August 2020) - Gerstenecker, Adam; Gammon, Meredith; Marotta, Dario; Fiveash, John; Nabors, Burt; Mulhauser, Kyler; Triebel, Kristen
Abstract: Objective: Impairment in the ability to provide informed consent is common in persons with brain metastasis. However, little is known about what factors contribute to this impairment in the patient group. Our objective is to determine if the associations between demographic, cognitive, and clinical variables correlate with the ability to provide informed consent in persons with brain metastasis. Methods: We administered a comprehensive neuropsychological battery to a group of 61 persons with brain metastasis. Demographic and clinical information was also collected. All diagnoses were made by board‐certified oncologists and were verified histologically. Statistical analyses included Pearson's product‐moment correlations, point biserial correlations, and linear regression. Results: Results indicated that combinations of education, verbal memory, executive function, whole brain radiation therapy, and chemotherapy affected various aspects of the ability to provide informed consent. Subsequent regression models demonstrated that these variables contributed a significant amount of shared variance to the ability to provide informed consent. Conclusion: We found that the ability of persons with brain metastasis to provide informed consent is a cognitively complex ability that is also affected by education and treatment variables. This information can help clinical researchers in identifying persons with brain metastasis at risk of an impaired ability to provide informed consent and aid in the consenting process.